In Quest of Mother’s Worth: How Millennial Instamoms’ Sharenting Revisits Women’s Traditional Roles - Siahaan, Rony Agustino (JURNAL KOMUNIKASI INDONESIA, 2023)
This paper aims to investigate the performance of the so-called digital mothers "Instamom" in Indonesia in the cultural contradiction between the construction of women's subjectivity that commodifies motherhood and intersubjectivity as to fulfilling women’s traditional role. Using performativity theory, I argue that the phenomenon of Instamoms’ sharenting is a communicative practice in the digital space that demonstrates the performance of a fluid and dynamic maternal identity without rigid boundaries. This research applies a digital ethnography approach to the everyday life’s practices of Stay-At-Home-Mothers that focus on the complexities of women's experiences in engaging with social media throughout the transition to motherhood. For this reason, this study conducted in-depth interviews and collected digital data from Instagram accounts. The findings show becoming a SAHM is their resolution to negotiate the image of an "ideal mother" through the subjective performance of a "good mother" that emphasizes neoliberalist maternal femininity. Gradually, this practice creates a digital mother performance that fulfills the demands of self-governmentality to replace women’s past professional career through digital entrepreneurship and commodification maternal identity. In conclusion, by performing digital mother, women play a variety of roles as they look for new opportunities whilst their traditional role serves as the main framework.